Broadway, Port of Spain, Trinidad, B.W.I.- 25516 - (:unkn) unknown (My University, 2010)
A view which overlooks Broadway (formerly Almond Walk), located at the bottom or south end of Frederick Street.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Streets--Trinidad and Tobago; Broadway; Cities and towns--Trinidad and Tobago--Port of Spain; Street-railroads--Trinidad and Tobago; Architecture--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago